Parents' Perceptions of Children's School Readiness During and After the COVID-19 Pandemic - Raden Sri Martini Meilanie; Gunarti, Winda; Yaumil Hassan, Astari (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
Children's school readiness is important to discuss because learning loss is an obstacle in preparing early childhood to enter elementary school. This study aims to look at parents' perceptions of their children's readiness for school during and after the COVID-19 pandemic. This study uses a quantitative descriptive survey research design to collect measurable data for statistical analysis from a population sample. The results show that preparing children for school during and after the COVID-19 pandemic is very different from the usual practice. Parents are required to provide appropriate stimulation to children at home to replace the role of teachers at school and restore the motivation and willingness of children to enter elementary school. The perception of parents is certainly very influential on the stimulation that will be given to children. Keywords: early childhood education, parents’ perceptions, school readiness References: Alexander, K. L., Entwisle, D. R., & Olson, L. S. (2007). Lasting Consequences of the Summer Learning Gap. American Sociological Review, 72(2), 167–180. https://doi.org/10.1177/000312240707200202 Araújo, L. A. de, Veloso, C. F., Souza, M. de C., Azevedo, J. M. C. de, & Tarro, G. (2021). The potential impact of the COVID-19 pandemic on child growth and development: A systematic review. Jornal de Pediatria, 97(4), 369–377. https://doi.org/10.1016/j.jped.2020.08.008 Atkinsonová, R. L., Atkinson, R. C., SMITH, E. E., Herman, E., Bem, D. J., & Petržela, M. (1995). Psychologies. Victoria Publishing. https://books.google.co.id/books?id=Tj9OAAAACAAJ Bao, X., Qu, H., Zhang, R., & Hogan, T. P. (2020). Modeling Reading Ability Gain in Kindergarten Children during COVID-19 School Closures. International Journal of Environmental Research and Public Health, 17(17). https://doi.org/10.3390/ijerph17176371 Benner, A. D., & Mistry, R. S. (2020). Child Development During the COVID-19 Pandemic Through a Life Course Theory Lens. Child Development Perspectives, 14(4), 236–243. https://doi.org/10.1111/cdep.12387 Brown, S. M., Doom, J. R., Lechuga-Peña, S., Watamura, S. E., & Koppels, T. (2020). Stress and parenting during the global COVID-19 pandemic. Child Abuse & Neglect, 110, 104699. https://doi.org/10.1016/j.chiabu.2020.104699 Colizzi, M., Sironi, E., Antonini, F., Ciceri, M. L., Bovo, C., & Zoccante, L. (2020). Psychosocial and Behavioral Impact of COVID-19 in autism spectrum disorder: An Online Parent Survey. Brain Sciences, 10(6). https://doi.org/10.3390/brainsci10060341 Creswell, J. W. (2015). Educational research: Planning, conducting, and evaluating quantitative and qualitative research (Fifth edition). Pearson. Cushon, J. A., Vu, L. T. H., Janzen, B. L., & Muhajarine, N. (2011). Neighborhood Poverty Impacts Children’s Physical Health and Well-Being Over Time: Evidence from the Early Development Instrument. Early Education and Development, 22(2), 183–205. https://doi.org/10.1080/10409280902915861 Duncan, R. J., Duncan, G. J., Stanley, L., Aguilar, E., & Halfon, N. (2020). The kindergarten Early Development Instrument predicts third grade academic proficiency. Early Childhood Research Quarterly, 53, 287–300. https://doi.org/10.1016/j.ecresq.2020.05.009 Engzell, P., Frey, A., & Verhagen, M. D. (2021). Learning loss due to school closures during the COVID-19 pandemic. Proceedings of the National Academy of Sciences, 118(17), e2022376118. https://doi.org/10.1073/pnas.2022376118 Friedman, M. M., Bowden, V. R., & Jones, E. (2003). Family Nursing: Research, Theory & Practice. Prentice Hall. https://books.google.co.id/books?id=mkBtAAAAMAAJ Gobbi, E., Maltagliati, S., Sarrazin, P., di Fronso, S., Colangelo, A., Cheval, B., Escriva-Boulley, G., Tessier, D., Demirhan, G., Erturan, G., Yüksel, Y., Papaioannou, A., Bertollo, M., & Carraro, A. (2020). Promoting Physical Activity during School Closures Imposed by the First Wave of the COVID-19 Pandemic: Physical Education Teachers’ Behaviors in France, Italy and Turkey. International Journal of Environmental Research and Public Health, 17(24). https://doi.org/10.3390/ijerph17249431 Griffith, A. K. (2020). Parental Burnout and Child Maltreatment During the COVID-19 Pandemic. Journal of Family Violence. https://doi.org/10.1007/s10896-020-00172-2 Hevia, F. J., Vergara-Lope, S., Velásquez-Durán, A., & Calderón, D. (2022). Estimation of the fundamental learning loss and learning poverty related to COVID-19 pandemic in Mexico. International Journal of Educational Development, 88, 102515. https://doi.org/10.1016/j.ijedudev.2021.102515 Jandrić, P. (2020). Postdigital Research in the Time of Covid-19. Postdigital Science and Education, 2(2), 233–238. https://doi.org/10.1007/s42438-020-00113-8 Kuhfeld, M., Tarasawa, B., Johnson, A., Ruzek, E., & Lewis, K. (2020). Initial findings on students’ reading and math achievement and growth. 12. Maldonado, J. E., & De Witte, K. (2022). The effect of school closures on standardised student test outcomes. British Educational Research Journal, 48(1), 49–94. https://doi.org/10.1002/berj.3754 McDowell, K., Jack, A., & Compton, M. (2018). Parent Involvement in Pre-Kindergarten and the Effects on Student Achievement. The Advocate, 23(6). https://doi.org/10.4148/2637-4552.1004 Nevid, J. S. (2012). Psychology: Concepts and Applications. Wadsworth Cengage Learning. https://books.google.co.id/books?id=TpxZXwAACAAJ Skulmowski, A., & Rey, G. D. (2020). COVID-19 as an accelerator for digitalization at a German university: Establishing hybrid campuses in times of crisis. Human Behavior and Emerging Technologies, 2(3), 212–216. https://doi.org/10.1002/hbe2.201 Spinelli, M., Lionetti, F., Pastore, M., & Fasolo, M. (2020). Parents’ Stress and Children’s Psychological Problems in Families Facing the COVID-19 Outbreak in Italy. Frontiers in Psychology, 11, 1713. https://doi.org/10.3389/fpsyg.2020.01713 Yoshikawa, H., Wuermli, A. J., Britto, P. R., Dreyer, B., Leckman, J. F., Lye, S. J., Ponguta, L. A., Richter, L. M., & Stein, A. (2020). Effects of the Global Coronavirus Disease-2019 Pandemic on Early Childhood Development: Short- and Long-Term Risks and Mitigating Program and Policy Actions. The Journal of Pediatrics, 223, 188–193. https://doi.org/10.1016/j.jpeds.2020.05.020